The Impact of Agile Project Management on the Effective Delivery of Innovative Products - Sowaidan, Amna (2016)
In the recent years organization are focusing on delivering innovative products to gain a competitive advantage in the market with the other organizations, therefore some organizations are shifting from traditional project management to agile project management. Agile project management emerged from the need of having a flexible development method that enables the organization to develop innovative products that satisfy the customers and return value to the organization, as opposed to traditional methods that consist of steps that could pose an obstacle in case a change emerged. This research paper focuses on the relationship between the use of agile project management and product innovation, through the examined case studies and questionnaire finding innovation can be achieved by using agile management with the support of users engagement in the development process and also with the association of skilled team members and effective management and with using advanced tools. In order to support agile principles several recommendation were presented that could be adopted by organizations to be innovative and achieve high user satisfaction.